Rehabilitation of Problematic and Degraded Lands through Forages - Hazra, C.R. (Journal of Soil and Water Conservation, 2022)
An estimated area of about 175 million hectares (m ha) of land is suffering from various land degradation problems including about 25 in ha of land is affected with local and different land management problems. The problem soils are especially of great concern for its. restoration and use per se. Forages are the best plant and vegetational materials indicating wide scope for the productive use of these habitats including rehabilitation and restoration of these eco-sites which may ultimately lead to reclamation and improvement and be suitable for future production of arable crops. Improvement of these specific ecosites including degraded lands are highlighted in this paper for possible use for forage production and soil productivity improvement.